Poverty and labor informality in Colombia - Roberto Mauricio Sánchez Torres (IZA Journal of Labor Policy, 2020)
Labor informality and poverty are at high levels in Latin America. In developing countries, poverty and the labor market are related not through unemployment but through employment. The purpose of this paper is to analyze the link between labor informality and poverty in Colombia. To do so, earnings gaps associated with labor informality are estimated; then, the effect of formalization on poverty is calculated, as the influence of changes in labor informality on Colombia's poverty reduction from 2002 to 2013. The findings show that the earnings gap between formal and informal workers is 37-44%, and if informality were eliminated, poverty would decrease by approximately 40%. However, even though informality has great potential to reduce poverty, its actual effect on Colombia's poverty reduction in the years analyzed was low.
Keywords: I32; J31; J46; 330; poverty; Colombia; labor informality; earnings gaps; selection bias